2/3y-9=-1

Simple and best practice solution for 2/3y-9=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2/3y-9=-1 equation:



2/3y-9=-1
We move all terms to the left:
2/3y-9-(-1)=0
Domain of the equation: 3y!=0
y!=0/3
y!=0
y∈R
We add all the numbers together, and all the variables
2/3y-8=0
We multiply all the terms by the denominator
-8*3y+2=0
Wy multiply elements
-24y+2=0
We move all terms containing y to the left, all other terms to the right
-24y=-2
y=-2/-24
y=1/12

See similar equations:

| 2n-6=28n | | 4+16=3x+2 | | 4=60/y | | (9n+12)+(15n-6)=180 | | 4b^2+5b=0 | | 21x+50=491 | | 19x-28=143 | | 7k/2+9=23 | | 3(31)-3=15x | | 3m/5=11 | | 3x+1/7 −32−4x/3 =145x−4​/14 +67x/6 | | 3(b-1)=2(b+1) | | 5.5=1.1/a | | 37=w-34 | | 3/4x+8-9/4x-5=6 | | ½x-3=x+6 | | a-13=21 | | 8.56-f=4.55 | | 9=7/8-2-1/8x | | 4x−5=4x+8 | | 3x+20.5=121 | | 9=7/8x-2-1/8x | | -8x+8+10x=-2 | | 2/(x+7)=3/(x+10) | | 3x+21.5=121 | | 4n^2=8n-2 | | 2x=6=2(3=x) | | 5x+60=x^2+10 | | 5(g-3)+2=(3G+1 | | 12x-12=24x-12 | | (u-6)^2=64 | | 2q^2+2=27 |

Equations solver categories